Elucidating the mechanism of triphenyl phosphate interference in bone metabolism via network toxicology and molecular docking methodologies - Xu, Min; Wu, Yinxiang; Meng, Jiaqi; Chen, Mengchen; Ding, Chen (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to elucidate the molecular mechanisms by which the widely used organophosphate flame retardant and plasticizer, triphenyl phosphate (TPhP), disrupts bone metabolism, highlighting the potential impact of environmental chemicals on bone homeostasis.MethodsA combined approach of network toxicology and molecular docking was employed to investigate the molecular mechanisms underlying the effects of TPhP on bone metabolism. Potential targets associated with both TPhP and bone metabolism were identified through database searches in ChEMBL, STITCH, GeneCards, and OMIM. A protein–protein interaction (PPI) network was constructed using the STRING database and analyzed with Cytoscape software. Functional enrichment analyses, including Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, were performed to determine the major pathways involved. Molecular docking was conducted to evaluate the binding affinity between TPhP and key target proteins. Additionally, in vitro experiments using MC3T3-E1 osteoblasts were conducted to validate the bioinformatics findings.Results78 potential targets related to both TPhP and bone metabolism were identified. STRING and Cytoscape revealed six key proteins: IGF1R, NR3C1, MAP3K1, BRAF, WNK4, and CNR2. GO and KEGG analyses indicated that these targets predominantly function through the MAPK signaling pathway. Molecular docking results demonstrated strong binding affinities between TPhP and key targets, particularly BRAF and WNK4. In vitro, TPhP inhibited osteoblast proliferation and migration in a dose-dependent manner and downregulated EMT-related proteins and key target genes via MAPK signaling.ConclusionTPhP disrupts bone metabolism by modulating key proteins and pathways, underscoring its potential health risks and the need for further epidemiological and clinical research.